MENINGKATKAN HASIL BELAJAR BULU TANGKIS MELALUI PENDEKATAN BERMAIN TIK-TOK SISWA KELAS V MI NAHDATUL ULAMA 01 KALADAWA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The Problem from this research is formulated “how efforts increases result learns badmintonpasses to approach to play tik-tok in class student V MI Nahdatul Ulama teacher 01 kaladawaschool year Tegal regency gargoyle district 2012/2013. Research kind that used researchaction class that consist of 2 cycles. Every cycle consists of planning, action execution, observation,and reflection. Approach that research qualitative and quantitative. watchfulness isdone at MI Nahdatul Ulama teacher 01 kaladawa Tegal regency, with class student researchsubject V with total 33 students, with carried out in may 2013. Instrument that used that isthat is sheet observai feasibility study, motivation observation sheet learns student, inquiryand student response and practice test. data analysis technique is done descriptively and passformula count that determined. research is said success if student achieves complete and resultlearns student from my cycle to cycle II. Research result demoes that badminton game studyapplications achievement with approach to play tiktok, in fifth year student of MI NahdatulUlama 01 Kaladawa Tegal Regency. Motivation learns student as a whole experience enhancedfrom my cycle to cycle ii. in pre cycle to my cycle is as big as that is from 15,3% is 30,3%.in cycle ii from 30,3% be 100%, so that in cycle is declared complete all 100%.